STRUCTURAL CHANGES OF ENDOCRINE SYSTEM OF MYOCARDIUM DURING THE STREPTOZOTOCIN DIABETES MELLITUS - Zhurakivska, O.Ya.; Mykulets, T.I.; Dutchak, U.M.; Klypych, Ya.I.; Miskiv, V.A.; Hrechyn, A.B.; Klypych, O.O. (World of Medicine and Biology, 2018)
The aim of the work was to establish the peculiarities of structural rearrangement of secretory atrial cardiomyocytes in the early and long-term streptozotocin diabetes mellitus (DM). DM was modeled by single intraperitoneal administration of streptozotocin (6 mg per 100 g of body weight). The material for the study was taken on the 14th and 56th days of the experiment. An electron microscope method of investigation was used. It was found that streptozotocin DM in secretory atrial cardiomyocytes leads to rearrangement of intracellular organelles responsible for the synthesis and secretion of atrial natriuretic peptide. It should be noted that there is a redistribution of various types of secretory granules (SG) in response to hyperglycemia. On the 14th day of experiment, there was a significant increase of the bulk density of diffusing SG, indicating the enhancement of withdrawal processes of ANP from the cell. On the 56th day, the bulk density of young and mature SG was significantly reduced, indicating a breakdown of compensatory mechanisms.